BALANCE SCORECARD DALAM ANALISIS MANAJEMEN PENDIDIKAN DI MI DARUL HIKMAH BANTARSOKA PURWOKERTO - Rizka Isnawati Fajrin (CV. Amerta Media, 2018)
Balance Scorecard is a management tool for maintaining a balance between financial and nonfinancial indicators, past performance indicators, present and future,internal and eksternal indicators. In BSC there are four perspectives to maintain balance in management. These four perspectives are financial, service, internal business and learning and growth perspective. MI Darul Hikmah implements school based management to improve the quality of education so it can optimally to avhieve the vision that has been determine. One form of improving the quality of education is by looking at school performance. Then school performance measurement can use balance scorecard approach. Key Words: Balance Scorecard, education management, MI Darul Hikmah